Marketing Issues in Transitional Economies - Batra, Rajeev (Springer US, 1999)
As the markets in transitional economies open and grow, major challenges and opportunities arise for multinational firms entering these markets, local firms facing these new competitors, and policymakers seeking to increase the ability of all firms to compete fairly and efficiently. Yet despite the important questions transition economies pose for policymakers and companies seeking to enter and compete in these new markets, there has been a relative absence of systematic research on these concerns. This book seeks to fill a gap in the existing literature by offering a pioneering and comprehensive examination of issues that have developed as markets in transitional economies become more deregulated and open. The countries discussed include China, the Czech Republic, Hungary, India, Poland, Romania, Russia, South Africa and South Korea.
Keywords: Marketing; Business and Management, general; Economic Growth; Business; Management science; Economic growth; Wirtschaftsreform; Konferenzschrift -- 1998 -- Ann Arbor Mich.